Quiste Epidermoide Intradiploico con Invasión Intracerebral: Reporte de Caso y Revisión de la Literatura - Pipolo, Derek Orlando (Revista Argentina de Neurocirugía, 2021)
Introduction: Intradiploic epidermoid cysts account for 25% of intracranial epidermoid tumors and less than 0.25% of all primary intracranial tumors. The most common locations are the frontal and parietal bone. Intradural extension is very infrequent, representing only 3%. Case Report: A 64-year-old female with a history of a frontal TBI at 11 years of age consulted for a left frontal subcutaneous tumor measuring 5 x 4 cm of prolonged evolution. Brain CT showed a lytic calvarial lesion associated with subgaleal involvement, intradural invasion and intraparenchymal extension. Surgical treatment of the tumor with its pseudocapsule was performed. The pathological report revealed an epidermoid cyst. Discussion: Epidermoid cysts can be congenital or acquired. Like our case, acquired types are usually caused by traumatic inclusion of the superficial epithelium. They tend to present as subcutaneous swelling and remain asymptomatic for decades. The unusual intradural extension can lead to symptoms such as seizures and neurological deficits. Treatment is usually complete resection together with its capsule in order to achieve a favorable prognosis and prevention of complications. Conclusion: Intradiploic epidermoid cysts are benign, slow-growing lesions that can reach considerable size and occasionally extend intracranially. Its diagnosis is usually suspected radiologically and confirmed by histopathological study. These should be included in the diagnostic algorithm of patients presenting single calvarium lesions with osteolysis and intradural invasion. In cases of intradural extension, total removal is insisted in order to prevent recurrence and potential malignancy.